Effect of replacement strike-face material on the ballistic performance of multi-ply soft armor targets. Issue 5 (March 2019) - Guo, Zherui; Chen, Weinong; Zheng, James
In this study, the impact-face material of a multi-ply soft armor system was varied to different ratios and tested for the effects on the ballistic performance. It is known that the first few layers of multi-ply soft armor material typically fail inelastically near the system ballistic limit and can be replaced with a "sacrificial" material with other more desirable properties. Previous studies have determined that the ballistic performance of these hybrid systems is largely dependent on the amount of high-performance backing material. However, the extent to which the high-performance fabric can be replaced has yet to be fully quantified and examined. Materials of different properties, namely stainless steel mesh, Makrolon® polycarbonate sheets, and cotton, were used as replacement frontal material for 840 d Twaron® panels, and the hybrid panels were impacted by O1 tool steel right-circular cylinder projectiles fired using a single-stage smooth-bore gas gun. Results show that the ballistic performance is maintained up to a frontal material ratio of about 40%, and off-axis material properties play a role in energy dissipation.